2012
DOI: 10.1007/s00221-012-3025-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-modulation of stimulus rate and current from elevated baselines expands head motion encoding range of the vestibular prosthesis

Abstract: An implantable prosthesis that stimulates vestibular nerve branches to restore sensation of head rotation and vision-stabilizing reflexes could benefit individuals disabled by bilateral loss of vestibular sensation. The normal vestibular system encodes head movement by increasing or decreasing firing rate of the vestibular afferents about a baseline firing rate in proportion to head rotation velocity. Our multichannel vestibular prosthesis emulates this encoding scheme by modulating pulse rate and pulse curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 33 publications
9
39
1
2
Order By: Relevance
“…This finding was consistent with reports in chinchillas and monkeys, where PRM levels did not significantly affect peak eye velocities at similarly high baseline pulse rates (Davidovics et al 2012. Only patient 2 showed significant differences between some PRM levels, which were possibly facilitated by the large dynamic range in that patient.…”
Section: Effects Of Pulse Modulation On Peak Eye Velocitysupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was consistent with reports in chinchillas and monkeys, where PRM levels did not significantly affect peak eye velocities at similarly high baseline pulse rates (Davidovics et al 2012. Only patient 2 showed significant differences between some PRM levels, which were possibly facilitated by the large dynamic range in that patient.…”
Section: Effects Of Pulse Modulation On Peak Eye Velocitysupporting
confidence: 92%
“…In other studies, increasing pulse amplitude by 100% or more led to markedly larger peak eye velocities (Davidovics et al 2012, Nie et al 2013, Phillips et al 2015. Our patients, however, had limited dynamic ranges and thus only modest increases between medium and high PAM levels.…”
Section: Effects Of Pulse Modulation On Peak Eye Velocitymentioning
confidence: 47%
“…2). A possible explanation for this phenomenon (when observed in chinchillas) was offered by Davidovics et al (2012). They suggested that increasing either current amplitude or pulse rate may increase the total number of action potentials (AP) firing on a vestibular afferent nerve since larger currents can increase the region of neural excitation, thereby recruiting more neural fibers to fire, and higher pulse rates can entrain a given population of nerve fibers to fire at higher frequencies (BeMent and Ranck 1969).…”
Section: Effects Of Velocity Encoding Strategy On Eye Responsesmentioning
confidence: 99%
“…Secondly, monkey eye movements were elicited using co-modulated stimuli, whereas chinchilla eye movements were elicited using rate-modulated stimuli. Since misalignment increases with increasing current Davidovics et al 2011Davidovics et al , 2012, it is likely that responses to co-modulating stimuli (which have varying current amplitudes) of different intensities would have different degrees of misalignment. Significant differences in response misalignment between different octants would necessitate eight unique transformation matrices to significantly improve alignment.…”
Section: Effects Of Alignment Precompensationmentioning
confidence: 99%
See 1 more Smart Citation